The Role of Trade and Offshoring in the Determination of Child Labour - Alessandro Cigno; Giorgia Giovannetti; Laura Sabani (Institute for the Study of Labor (IZA), 2015)
Incorporating family decisions in a two-period-model of the world economy, we show that trade liberalization may reduce child labour in developing countries where the initial share of skilled workers in the adult workforce though not as large as in developed countries is nonetheless large enough to attract skill-intensive FDI from the latter. If the production activities so relocated are more skill-intensive than those carried out in the destination countries before liberalization, that will in fact tend to offset the downwards pressure on the ratio of skilled to unskilled wage rates (Stolper-Samuelson effect), and thus on the incentive for parents to invest in their children's education, associated with international specialization. The hypothesis is not rejected by the data, and thus helps to explain why child labour has not risen in all developing countries, but risen in some and fallen in others.
Keywords: D13; D33; F16; J13; J24; 330; trade barriers; FDI; skill endowment; skill premium; school enrolment; child labour